Non-steroidal anti-inflammatory drugs (NSAIDs) as a hidden threat to scavenging raptors beyond Gyps: A call for wider research and surveillance - Colston, Kane (2025)
Asian vulture declines have been linked to the consumption of contaminated livestock carcasses with the non-steroidal anti-inflammatory (NSAID) diclofenac. Studies have suggested that the toxicity of NSAIDs to Old World vultures may be through an intronic premature termination codon (PTC) in the gene CYP2C19, encoding a cytochrome P450 enzyme thought responsible for diclofenac metabolism in vultures. However, it remains unclear whether this mechanism applies for all susceptible raptor species. We used nucleotide databases (NCBI) to compare the Cape vulture (Gyps coprotheres) CYP2C19 sequence to other vulture sequences to identify the presence of the intronic PTC. Our search revealed that only Gyps species possessed the CYP2C19 PTC. This is despite NSAID toxicity at similar contaminant levels found in non-Gyps accipitrid mortalities. Our findings suggest avian scavengers could be affected by additional toxicological mechanisms, including sublethal toxicity. Further research is required to establish such mechanisms and exposure risk in non-Gyps scavengers.